Dendistry and Modernity: Case Reports by Brazilian Based on Professional Experiences - Alves da Costa, Luciana (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
The purpose of this article is to show the development of a project carried out in the research line of Oral History and Health Narratives, at the Centro de História e Filosofia das Ciências da Saúde (CeHFi), (Health Sciences History and Philosophy Center) at Unifesp. The work has been developed from the narrative of dentists and collaborators, which has resulted in a pre-analysis on the thinking of modern dentists, regarding their dilemmas and challenges when conducting 'the art of dentistry' at a time in history where dental practice is fully mediated by science and technology. Questions such as humanization versus dehumanization of dentistry, and aspects related to the work environment, are addressed and lead to reflection in this work.